A NMR-Based Metabolomic Approach to Investigate the Antitumor Effects of the Novel [Pt(η1-C2H4OMe)(DMSO)(phen)]+ (phen = 1,10-Phenanthroline) Compound on Neuroblastoma Cancer Cells - Federica De Castro; Erika Stefàno; Erik De Luca; Antonella Muscella; Santo Marsigliante; Michele Benedetti; Francesco Paolo Fanizzi (Bioinorganic Chemistry and Applications)
NMR-based metabolomics is a very effective tool to assess the tumor response to drugs by providing insights for their mode of action. Recently, a novel Pt(II) complex, [Pt(ƞ1-C2H4OMe)(DMSO)(phen)]+ (phen =  1,10-phenanthroline), Pt-EtOMeSOphen, was synthesized and studied for its antitumor activity against eight human cancer cell lines. Pt-EtOMeSOphen showed higher cytotoxic effects than cisplatin in most of the cancer cell lines and in particular against the neuroblastoma cell line (SH-SY5Y). In this study, the mechanism of action of Pt-EtOMeSOphen on SH-SY5Y cells was investigated using 1H NMR-based metabolomics and compared with cisplatin. The observed time response of SH-SY5Y cells under treatment revealed a faster action of Pt-EtOMeSOphen compared with cisplatin, with a response already observed after six hours of exposure, suggesting a cytosolic target. NMR-based metabolomics demonstrated a peculiar alteration of the glutathione metabolism pathway and the diacylglycerol expression.